FORMULASI NANOPARTIKEL KITOSAN EKSTRAK METANOL ALGA LAUT COKLAT (Sargassum hystrix) DENGAN METODE GELASI IONIK - Agung Giri Samudra; Nurfijrin Ramadhani; Fathnur Sani K; Gina Lestari; Bambang Hernawan Nugroho (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2021)
The content of marine algae Sargassum hystrix includes polysaccharides (alginates), polyphenols, proteins, peptides, amino acids, lipids, minerals, and several vitamins. However, the use of natural ingredients has limitations, namely that it often fails in the clinical phase due to low bioavailability. One effort that can be done to overcome this problem is to formulate nanoparticles using chitosan polymer and sodium tri-polyphosphate. This study aims to formulate nanoparticles from the methanol extract of Sargassum hystrix with various chitosan concentration ratios. The methanol extract of Sargassum hystrix was obtained by extraction using the maceration method with 50% methanol as a solvent. The results of the extract were made colloidal nanoparticles using ionic gelation techniques using a variation of the methanol extract of Sargassum hystrix: chitosan: NaTPP: Tween 80, Formulation 1 (0.75 gram: 0.1% 18 mL: 0.1% 9 mL: 0.5% 3 mL); Formulation 2 (0.75 gram: 0.2% 18 mL: 0.2% 9 mL: 0.5% 3 mL); Formulation 3 (0.75 gram: 0.1% 18 mL: 0.2% 9 mL: 0.5% 3 mL); Formulation 4 (0.75 gram: 0.2% 18 mL: 0.1% 9 mL: 0.5% 3 mL). The nanoparticle colloids formed were characterized by particle size (nm), and the zeta potential (mV), Formula 1 (212.65 ± 45.32; -11.4 ± 5.65), Formula 2 (514.55 ± 56.35; -8.85 ± 1.34), Formula 3 (219.35 ± 43.76; -14.5 ± 1.83), Formula 4 (326.5 ± 3.39; -1.25 ± 17.88). All formulas show that they can form nanoparticle formulas between 1-1000 nm., But the preparation that will be more stable is formula 3 because it has a zeta potential that is close to +/- 30 mV.